Pesantren Concepts for Producing Quality Graduates - Ruhiyat, Ruhiyat; Didin Saepudin; Nirwan Syafrin; Handrianto, Budi (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2024)
This research is intended to find out the concept of pesangren in producing quality graduates, conducted at the Thawalib pesantren in West Sumatra. From January 2022 to July 2023, with the teachers. The results showed that Thawalib pesantren in producing quality graduates through the concept of pesantren; determining the value of pesantren, modernizing pesantren, collaborating with the community, financial transparency and open pesantren for the understanding of various streams.